2003
DOI: 10.1007/s10595-002-2511-2
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid-Squamous Carcinoma of the Esophagus Treated by Preoperative Chemotherapy: Report of Two Cases

Abstract: Basaloid squamous carcinoma (BSC) of the esophagus has been associated with a poor outcome after surgery. We herein report two patients with esophageal BSC treated by preoperative chemotherapy. Patient 1 was a 55-year-old man who presented with a tumor of the middle esophagus diagnosed as BSC. He was treated by chemotherapy using a combination of 5-fluorouracil (5-FU: 750 mg/m(2), 1st-5th day, 24-h continuous infusion) and cisplatin (CDDP: 75 mg/m(2), 1st day, drip infusion per 2 h) before surgery, because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Basaloid squamous cells carcinoma is treated with surgery, radiotherapy, or both, with or without chemotherapy (5-fluorouracil and cisplatin). [2][3][4] p63 was discovered in a screen for p53-homologous genes. Like p53, p63 codes for proteins with an amino(N)-terminal transcription-activating region, a middle DNA-binding region, and a carboxyl terminal region responsible for oligomerization.…”
mentioning
confidence: 99%
“…Basaloid squamous cells carcinoma is treated with surgery, radiotherapy, or both, with or without chemotherapy (5-fluorouracil and cisplatin). [2][3][4] p63 was discovered in a screen for p53-homologous genes. Like p53, p63 codes for proteins with an amino(N)-terminal transcription-activating region, a middle DNA-binding region, and a carboxyl terminal region responsible for oligomerization.…”
mentioning
confidence: 99%
“…Since Yamamoto et al reported the first case of BSC of the esophagus in 1979 [2], approximately 60 cases of BSC have been reported, mainly from Japanese institutions [3][4][5][6][7][8]. The prognosis of BSC is poor, but it remains controversial compared with SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of superficial-type BSC having invaded the submucosal layer, the therapeutic effectiveness of surgery alone was reported for some cases [4,5]. Advanced cases of BSC accounting for most patients result in dismal outcomes owing to high rates of rapid and widespread nodal and organ metastases, regardless of curative resection or adjuvant therapy [4,6,8,9]. Sarbia et al reported that there is no difference in the overall survival rate between typical BSC and SCC, being 38.5% and 39.3% after 2 years and 19.2% and 19.0% after 5 years, respectively [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autores japoneses preconizam quimioterapia com 5-Fluoracil e cisplatina para os tumores localmente avançados, sem metástases à distância 4,7 . Esta conduta visa reduzir as dimensões da lesão primária, de modo a viabilizar a realização da esofagectomia associada a linfadenectomia em três campos: cervical, torácico e abdominal, com razoável índice de sobrevida.…”
Section: Relato Do Casounclassified